De l’ethnographie critique des archives à la modélisation d’une base de données pour l’étude de l’Iran postrévolutionnaire - Natalia Pashkeeva; Chowra Makaremi; Johanna Saadoune (Revue des Mondes Musulmans et de la Méditerranée)
The history of revolutionary violence in Iran is not linked as much to the struggles that led to the overthrow of the Shah in 1979 as to the solidification of the Islamic republican regime in the 1980s. Our collective, interdisciplinary research on this under-studied period explores the connections between violence, the construction of the post-revolutionary nation-state in Iran, and national and transnational memorial policies. We have created a database cataloguing the various sources, archives, and counter-archives of the long Iranian revolution, stored in repositories and accessible to researchers, or disseminated online through various networks of memorial activism. This article discusses the analytical, methodological and technical aspects of database production, exploring both conceptual and administrative issues. Their interrelations reveal the political stakes of research in Digital Humanities and project-based research.